Influencia de la tecnologia en los precios de venta de muebles de una carpinteria de la ciudad de Huamachuco. - Siccha Samana, Hilda Violeta (2011)
The present work of investigation treats to near "Influence of the Technology in the Prices of Sale of Furniture of a Carpentry of Huamachuco's City". The scientific methods used in the investigation were: analytical method - synthetic and inductive deductive; also one used instruments of compilation of information as the observation, and the application of surveys and interviews. These instruments were applied to the participants of the carpentry. An analysis was realized to the carpentry to determine the condition in the one that is and to affect a diagnosis of the technology that it uses for the manufacture of his products. Finally one presents a list of checks realized to the carpentry to determine the influence of the technology. The investigation gave as result that the technology used in "Carpentry San Pedro" if it influences directly the prices of sale of furniture.